A Novel Wireless 3D Localization Method Supported by WSN - Liu, Jianqi; Wang, Qinruo; Chen, Xiaohu; Huang, Wanghua (International Journal of Online and Biomedical Engineering (iJOE), 2013)
In many applications, the location information should be necessary. This paper propose a cheap multi-plane 3D localization solution, which based on the existing 2D localization system, a perpendicular 2D plane is added to achieve 3D localization. The algorithm is intended for applications which require information of the height, but remain less sensitive to the location accuracy. At the same time, this paper also introduces symmetrical double-sided two-way ranging (SDS-TWR) and dynamic power consumption intensity searching algorithm into localization system, which can effectively lessen the influence of time synchronization and ease internet traffic congestion of wireless localization network.